2014
DOI: 10.1080/10826076.2013.803204
|View full text |Cite
|
Sign up to set email alerts
|

Group Separation of Heavy Metals Followed by Subsequent and Individual Separation of Lanthanides by Chelation Chromatography

Abstract: A new method was developed for group separation of some heavy metals (HM) from rare earth elements (REEs) followed by online individual separation of REEs. Various chelating agents were used as mobile phases such as DTPA, PDCA, NTA, HIBA and oxalic acid. These chelating agents were selected with different number of carboxylic acid groups and various geometrical structures which control the elution capability and the separation efficiency. The results showed that selective group separation of HM from REEs could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a past work [28], the author has been capable, through utilizing a blend of oxalic and diglycolic acids along with nanopure water as a mixed eluent, to separate the rare earth elements (REEs) (La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu) through a gradient elution method Figure (1). This has certainly been done before by introducing PDCA eluent with a concentration of 7 mM at pH 3.95 so as to initially elute the heavy metals (Fe +3 , Cu +2 , Ni +2 , Zn +2 , Cd +2 , Mn +2 ), in a way to keep away from any conceivable interference with the lanthanides elution and separation [29,30]. As indicated from the demonstrated work, Y was coeluted in one peak with Dy, so in the present work, many trials were done to solve the problem of separation of Y from Dy simultaneously with individual separation of the other thirteen RREs, including variation in the oxalic acid / diglycolic acid eluents concentration ratio, its introducing time and gradient flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…In a past work [28], the author has been capable, through utilizing a blend of oxalic and diglycolic acids along with nanopure water as a mixed eluent, to separate the rare earth elements (REEs) (La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu) through a gradient elution method Figure (1). This has certainly been done before by introducing PDCA eluent with a concentration of 7 mM at pH 3.95 so as to initially elute the heavy metals (Fe +3 , Cu +2 , Ni +2 , Zn +2 , Cd +2 , Mn +2 ), in a way to keep away from any conceivable interference with the lanthanides elution and separation [29,30]. As indicated from the demonstrated work, Y was coeluted in one peak with Dy, so in the present work, many trials were done to solve the problem of separation of Y from Dy simultaneously with individual separation of the other thirteen RREs, including variation in the oxalic acid / diglycolic acid eluents concentration ratio, its introducing time and gradient flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…In analogy, elements with smaller ionic charge or larger ionic radius than the lanthanides (e. g. alkali and alkaline earth metals, transition metals) tend to be retained on the cation exchange resin. It has been shown that the elution of Mn 2+ , Co 2+ and Ni 2+ from the resin with α-HIBA might coincide with the desired lanthanide element [25]. Nevertheless, these elements have low affinity towards the LN resin.…”
Section: Introductionmentioning
confidence: 99%